2014
DOI: 10.1016/j.jvs.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Custom-made versus off-the-shelf multibranched endografts for endovascular repair of thoracoabdominal aortic aneurysms

Abstract: The t-branch device, with the unique advantage of direct implantation without any delay for manufacturing, showed 100% technical success and comparable clinical outcomes to the traditional custom-made mbEVARs. Further long-term evaluation remains mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 16 publications
3
79
0
Order By: Relevance
“…1,3 Device characteristics and implantation. A custommade device (fenestrated, branched, or combined; Cook Medical Inc, Bloomington, Ind) was used for the elective cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Device characteristics and implantation. A custommade device (fenestrated, branched, or combined; Cook Medical Inc, Bloomington, Ind) was used for the elective cases.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 The great expectation was that the minimally invasive character of the procedure (no visceral ischemia and no aortic clamping) would not only provide a survival benefit but also prevent spinal cord ischemia (SCI). However, the first series of TAAAs treated endovascularly could not support this hypothesis.…”
mentioning
confidence: 99%
“…Preliminary series have provided good short-term results. Bisdas et al 2 recently reported their experience with custom made and off the shelf (t-branch) multibranched Cook devices. The t-branch device showed 100% technical success and similar clinical outcomes to the custom made device.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Therefore, some patients will still require custom made stent grafts. In their study, Bisdas et al 2 also identified the main obstacles that would make the t-branch unsuitable for implantation: distance between the celiac trunk and the most caudal renal artery >56 mm, insufficient luminal diameter (<25 mm) at the level of the visceral arteries, upward orientation of at least one renal artery, and a distance 67 mm between the most caudal renal artery and the aortic bifurcation. 2 Bisdas et al 2 also reported the availability of four target vessels accessible from an antegrade approach as being an anatomic inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…The closure of the cuff is not mentioned in the IFU, however described in the literature by the application of "coils" [16]. Bisdas et al [17] compared results of the application CMD and t-Branch endograft in elective patients with TAAA. Although perioperative success was complete in both groups, mortality was higher in group treated with CMD (p = 0.04).…”
Section: Discussionmentioning
confidence: 99%